VOICES OF RUDARI WOMEN FROM FILIAŞI (ROMANIA) IN THE CONTEXT OF CONVERSION TO PENTECOSTALISM - GIRIGAN, Gabriel (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Voices of Rudari women from Filiaşi (Romania) in the Context of Conversion to Pentecostalism. The present article examines conversion to Pentecostalism among Rudari women in post-socialist Eastern Europe. The case study focuses on a Rudari ethnic community located in a small town in southern Romania and shows that Rudari women assume a dual role: one involves preserving the interplay between Pentecostalism and local culture, while the other entails initiating conversion among men. Women facilitate conversion through visions, dreams, or manifestations of illness, which position them as gatekeepers who translate Pentecostalism into the local cultural context. Furthermore, women serve as guides for men undergoing conversion, playing a vital role in bridging the gap between Rudari traditions and the Pentecostal culture. They demonstrate proficiency in interpreting Pentecostal ecstatic phenomena within their predominantly male community, with their voices serving as mediators throughout the conversion process (Brusco, 2010). Similarly, women act as “therapists,” facilitating men’s conversion and addressing issues related to the transformation of traditional notions of masculinity. Voci ale femeilor rudărese din Filiași (România) în contextul convertirii la penticostalism. Articolul de față prezintă convertirea la penticostalism în rândul femeilor dintr-o comunitate de rudari în contextul postsocialismului est-european. Studiul de caz prezintă o comunitate etnică de rudari dintr-un oraș mic din sudul României. Argumentez că femeile rudărese au un dublu rol în comunitate, primul de conservare a dualismului dintre penticostalism și cultura locală și al doilea de inițiere a convertirii în rândul bărbaților. Femeile alimentează convertirea religioasă prin viziuni, vise sau semne de boală. Toate aceste condiții prealabile au facilitat devenirea lor ca interprete ale traducerii penticostalismului în cultura locală. Mai mult decât atât, femeile devin astfel călăuze ale convertirii bărbaților. Ele joacă, de asemenea, un rol important în medierea celor două lumi, tradițiile Rudari și noua cultură penticostală. Ele sunt capabile să descifreze semnele extatice penticostale într-un context comunitar dominat de bărbați, vocile femeilor devenind astfel un mediator în procesul de convertire (Brusco, 2010). În mod similar, femeile acționează ca „terapeute” în contextul procesului de convertire și transformare a machismului bărbaților. Cuvinte-cheie: Penticostalism, România, studii asupra băieşilor/rudarilor, transformare culturală, naraţiuni ale convertirii, studii de gen, etnografie Article history: Received 09 October 2023; Revised 14 May 2024; Accepted 19 May 2024; Available online 25 June 2024; Available print 30 June 2024.